Systematic review of compression following treatment for varicose veins. Issue 7 (2nd April 2015) - El‐Sheikha, J.; Carradice, D.; Nandhra, S.; Leung, C.; Smith, G. E.; Campbell, B.; Chetter, I. C.
<x xml:space="preserve">Abstract</x> Background Consensus regarding compression following treatment of varicose veins has yet to be reached. This systematic review aims to establish the optimal compression regimen after venous treatment. Methods A systematic review of MEDLINE, Embase and CENTRAL was performed to identify randomized clinical trials (RCTs) investigating different compression strategies following treatment for superficial venous insufficiency. Results Seven RCTs comparing different durations and methods of compression fulfilled the inclusion criteria. The treatment modality was open surgery in three trials, foam sclerotherapy in two and endovenous laser ablation (EVLA) in two trials. The quality of the studies was variable, and significant sources of potential bias were present. Both the studies and compression regimens used were heterogeneous. Ten products were used in six general regimens for a duration of 0–42 days. One study suggested that 7 days rather than 2 days of stockings following EVLA was associated with superior quality of life and less pain at 1 week. Another study reported that, following surgery, application of a compression stocking after 3 days of bandaging was associated with a slightly longer recovery than no compression after 3 days. One study recorded compliance clearly, finding it to be only 40 per cent. The quality and heterogeneity of the studies precluded meta‐analysis. Conclusion There is currently little quality evidence upon which to base any recommendations concerning compression following treatment for varicose veins.